Digital and physical re-creation of ancient Chinese bells: new understandings and discoveries - Kin Sum Li (Humanities & Social Sciences Communications)
Abstract Previous research has focused primarily on replicating bells that were expected to resemble the original closely in terms of material, size, shape, and tone. There has, however, been no effort to use original bells as templates from which to re-create or re-design new bells that deviate significantly in size, yet maintain the shape of the originals in order to address issues in the history of art and in the archeology of ancient China. Experimentation with ancient bells in this field remains largely untapped. This article proposes to re-create bells in enlarged and reduced sizes through casting, based on 3D-printed resin models that have been correspondingly scaled up and down, from a 3D model scanned from a 500 BCE bell that was excavated from Xinzheng in Henan province, China. The study seeks to answer a series of questions, including whether replication of bells was practiced in ancient times, how casters could predict the tones a bell would produce before casting, and how a set of bells used as a musical ensemble could have been developed over history.